Enhanced Biogas Production from Tapioca Wastewater Through the Microbial Electrolysis Cell-Assisted Anaerobic Digestion Process at Various Urea Additions - Khomariah, Nur; Syaichurrozi, Iqbal; Kurniawan, Teguh (Jurnal Bahan Alam Terbarukan, 2024)
In Indonesia, tapioca wastewater is one of the most abundant organic wastewater. It has a great deal of potential for use as a substrate for biogas, but it contains a high ratio of chemical oxygen demand (COD) to nitrogen (N). For this reason, adding nitrogen sources, such as urea, is crucial. Meanwhile, microbial electrolysis cell-assisted anaerobic digestion (MEC-AD) is a novel technology that can be applied to enhance biogas production. Thus, the purpose of this study was to ascertain how adding urea affected the biogas yield from tapioca wastewater through the MEC-AD process. There were six digesters, namely A (MEC-AD urea 0.25 g), B (MEC-AD urea 0.5 g), C (MEC-AD urea 1 g), D (MEC-AD urea 1.5 g), E (MEC-AD without urea), F (AD without urea). The MEC-AD process was carried out at room temperature using a batch system. The results revealed that the MEC-AD (without urea) generated a biogas yield 2.3-fold higher than AD alone (without urea). Then, an increase in urea addition in the MEC-AD process from 0 to 1.5 g enhanced biogas yield from 106.4 to 268.8 mL/g-COD. It means that in MEC-AD, the urea addition of 1.5 g generated 2.5 times more biogas yield than without urea addition. The MEC-AD with urea addition of 1.5 g had the most stable substrate pH and the highest volatile fatty acids during the process. The MEC-AD (without urea) gave a higher COD removal efficiency (21%) than AD alone (without urea), namely 14%. Then, an increase in urea addition from 0 to 1.5 g in MEC-AD increased COD removal from 21% to 38%. Therefore, the best variable was MEC-AD with a urea addition of 1.5 g. This innovation is expected to reduce environmental pollution and provide biogas as alternative energy to substitute the use of fossil fuels.